1982
DOI: 10.1136/hrt.47.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory electrocardiographic recording in endurance athletes.

Abstract: Data from ambulatory electrocardiographic recording in 35 highly trained endurance athletes and in 35 non-athletic controls of similar ages are given. The minimal, mean hourly, and maximal heart rates were significantly lower in the athletes. Thirteen athletes (37 . 1%) but only two controls (5 . 7%) had sinus pauses exceeding 2 . 0 seconds. First degree atrioventricular block was observed in 13 athletes (37 . 1%) and five controls (14 . 3%), second degree Wenckebach type block in eight athletes (22 . 9%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(73 citation statements)
references
References 33 publications
3
67
1
2
Order By: Relevance
“…However, these findings were limited to a single‐center experience and were not in keeping with the results of old studies performed in the 1980s and 1990s, which demonstrated no differences in the VA burden at 24‐hour ambulatory electrocardiographic monitoring between athletes and sedentary individuals 6, 7, 8, 9, 10, 11. Moreover, these previous investigations focused on the number and complexity of VAs without characterizing the morphologic features of premature ventricular beats (PVBs), a parameter that may help to identify the site of origin of the arrhythmia and the possible underlying myocardial substrate 12…”
Section: Introductioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, these findings were limited to a single‐center experience and were not in keeping with the results of old studies performed in the 1980s and 1990s, which demonstrated no differences in the VA burden at 24‐hour ambulatory electrocardiographic monitoring between athletes and sedentary individuals 6, 7, 8, 9, 10, 11. Moreover, these previous investigations focused on the number and complexity of VAs without characterizing the morphologic features of premature ventricular beats (PVBs), a parameter that may help to identify the site of origin of the arrhythmia and the possible underlying myocardial substrate 12…”
Section: Introductioncontrasting
confidence: 51%
“…In this study, most athletes with VAs had no evidence of underlying structural abnormalities, the arrhythmias tended to decrease after detraining, and the follow‐up was uneventful: all these findings are consistent with the concept that VAs may be considered a feature of the “athlete's heart.”4, 5 Moreover, Palatini et al compared 40 endurance athletes with 40 sedentary individuals and found that the prevalence of complex VAs at ambulatory electrocardiographic monitoring was higher in trained individuals 10. Other studies comparing the prevalence of VA at 24‐hour ambulatory electrocardiographic monitoring in healthy athletes versus sedentary individuals disproved the concept of a proarrhythmic effect of sports activity by demonstrating that only a minority of athletes exhibited frequent or complex VAs with a prevalence that did not differ with that of their sedentary counterpart6, 7, 8, 9, 11 (Table S4). In addition, Delise et al reported that the proportion of athletes with VAs who showed a reduction in the arrhythmic burden during follow‐up was similar in a group undergoing detraining and in a group who continued training 21…”
Section: Discussionmentioning
confidence: 99%
“…21 However, in 35 adolescent and young adult male endurance athletes, sinus pauses of greater than 2 sec are documented in 37.1% of the subjects (vs. 5.7% of nonathlete controls). 22 Taken in perspective, large studies of healthy normal children and young adults rarely demonstrate sinus pauses or transient asystoles, with the exception of endurance athletes. However, small studies of children with CCHS (sample size 7-14 subjects), studied in an era before PHOX2B genetic testing, often had transient asystoles on Holter recording.…”
Section: Congenital Central Hypoventilation Syndrome (Cchs)mentioning
confidence: 99%
“…No presente trabalho, foram observadas assistolias (pausas maiores que dois segundos) em onze animais (27,5%) sendo que a maior pausa foi de 5 segundos; o nível de condicionamento físico C1 teve um efeito significativo sobre o número de assistolias e assim como o tempo de maior pausa em segundos, já que nesse condicionamento a média do número de assistolias foi de 14,9±3,6 e a mé-dia da maior pausa foi de 1,68±0,40 segundos, resultado inferior ao observado por Viitasalo et al (1982) em atletas humanos de endurance nos quais 37,1% apresentaram assistolias acima de 2 segundos. Na avaliação da morfologia da onda T foi observado que houve efeito significativo desses momentos e da altitude nos resultados da análise de variância, enquanto o condicionamento físico não teve efeito significativo em ambos os canais.…”
Section: Discussionunclassified